Understanding U.S. Wage Dynamics - Abdih, Yasser (IMF Working Papers; Working Paper, 2018)
In this paper, we undertake empirical analysis to understand U.S. wage behavior since the beginning of the new millennium. At the macroeconomic level, we find that a productivity-augmented Phillips curve model explains the data fairly well. The model reveals that the upward pressure on wage growth from recent tightening in the labor market has been dampened by a persistent decline in trend labor productivity growth and the share of income that accrues to labor. These themes are reinforced and complemented at the micro-economic level. Lower regional unemployment puts an upward pressure on wages of individuals, although this effect has become weaker since 2008. But there is downward pressure on wages for individuals with occupations that are exposed to automation and offshoring, and in industries with a higher concentration of large firms. All these factors appear to play a role illustrating why it is difficult to single out any one culprit for the observed wage growth moderation.